Rezension von: Metz, Friedrich (Hrsg.), Vorarlberg - Schahl, Adolf (Schwäbische Heimat, 1961)
Vorarlberg - Landschaft, Kultur, Industrie, hrsg. von Friedrich Metz, Jan Thorbecke-Verlag Lindau, 1960, DM 15.60.